Helminth Diversity in Teleost Fishes from the South Orkney Islands Region, West Antarctica - T. Kuzmina; O. Salganskiy; K. Vishnyakova; J. Ivanchikova; O. Lisitsyna; E. Korol; Yu. Kuzmin (zoodiversity, 2022)
Helminths of 12 fish species collected near South Orkney Islands, West Antarctica were studied. In the whole sample of 115 fish specimens, we identified one species of Monogenea, 5 species of Trematoda, 4 species of Cestoda, 5 species of Nematoda, and 7 species of Acanthocephala. All cestode species, 3 species of nematodes, and 5 species of acanthocephalans were represented only by larval stages; fish are definitive hosts for the remaining 10 helminth species. Details of composition and structure of helminth communities were studied in 3 fish species: Chaenocephalus aceratus (Lönnberg, 1906), Champsocephalus gunnari Lönnberg, 1905, and Pseudochaenichthys georgianus Norman, 1937, each represented by more than 20 specimens in a sample. In these hosts, 19, 8, and 16 helminth species were found, correspondingly. In the helminth communities of C. aceratus and P. georgianus, the highest values of the infection prevalence and abundance were recorded for larval cestodes (Diphyllobothrium sp., Tetrabothriidea), nematodes (Pseudoterranova sp., Contracaecum sp.), acanthocephalans (Corynosoma spp.), as well as adults of the trematode Neolebouria georgiensis Gibson, 1976. The same trematode species and larval cestodes predominated in the helminth community of C. gunnari. All recorded species of parasites are generalists, each known from a range of fish hosts in Antarctica.